2021
DOI: 10.1016/j.omtm.2020.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue-directed FGF21 gene therapy improves metabolic and immune health in BTBR mice

Abstract: Fibroblast growth factor 21 (FGF21) is a peptide hormone that serves as a potent effector of energy homeostasis. Increasingly, FGF21 is viewed as a promising therapeutic agent for type 2 diabetes, fatty liver disease, and other metabolic complications. Exogenous administration of native FGF21 peptide has proved difficult due to unfavorable pharmacokinetic properties. Here, we utilized an engineered serotype adeno-associated viral (AAV) vector coupled with a dual-cassette design to selectively overexpress FGF21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 81 publications
0
18
0
1
Order By: Relevance
“…FGF21 gene therapy is another way to overcome the unfavorable pharmacokinetic properties of native FGF21. Researchers administered an FGF21-overexpressing adeno-associated viral vector to mouse visceral adipose tissue, which decreases body weight and improves insulin sensitivity 130 . This study also highlights the potential of gene therapy to overexpress FGF21 in target tissues.…”
Section: Fgf21 and Metabolic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…FGF21 gene therapy is another way to overcome the unfavorable pharmacokinetic properties of native FGF21. Researchers administered an FGF21-overexpressing adeno-associated viral vector to mouse visceral adipose tissue, which decreases body weight and improves insulin sensitivity 130 . This study also highlights the potential of gene therapy to overexpress FGF21 in target tissues.…”
Section: Fgf21 and Metabolic Diseasesmentioning
confidence: 99%
“…One study reported that injection with a liver-specific FGF21 expression nonviral plasmid in FGF21 knockout mice can restore FGF21 expression and regulate body mass 174 . Another study utilized an adeno-associated viral vector to express FGF21 in mouse visceral adipose tissue, which resulted in reduced whole-body adiposity and adipose tissue macrophage inflammation 130 . Moreover, researchers recently designed a novel FGF21 named LAPS-FGF21 with a longer half-life via conjugation to the Fc fragment of IgG4, which has shown an excellent therapeutic effect on obesity in mice 175 .…”
Section: Fgf21 and Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, M2specific reduction of CD1d expression and alterations of APCs from M2 to M1 are important initiating events that switch iNKT cell-mediated immune responses from anti-inflammatory to proinflammatory activities and disrupt the immune balance in VAT of obese mice (23). AT-resident iNKT cells are also innate lipid sensors that play crucial roles in glycemic control and weight regulation in the steady state of VAT via the production of fibroblast growth factor 21 (FGF21) (24,25).…”
Section: Eosinophilsmentioning
confidence: 99%
“…Assim, aumentar a capacidade termogênica é apenas um dos efeitos que exerce63 . Para exemplificar, camundongos que expressam excessivamente FGF-21 no TAB-PE, mesmo na ausência de aumento na expressão da UCP1, apresentam redução da adiposidade total e da inflamação do TA, maior expressão de adiponectina e maior sensibilidade à insulina147 .Embora trabalhos na literatura tenham reportado o aumento da UCP1 no TAB-SC130,148,149 e no TAM149 de camundongos treinados com o HIIT, e no TAB-SC de camundongos treinados com o TFA74 , o conjunto de dados relacionados a capacidade termogênica dos três depósitos avaliados sugere que o HIIT não foi capaz de aumentá-la. O presente trabalho não é o primeiro a reportar a ausência de alterações na capacidade termogênica do TA com o HIIT.…”
unclassified